2019
DOI: 10.1017/s0021859619000376
|View full text |Cite
|
Sign up to set email alerts
|

First assessment of Goidanich Index and aerobiological data forPlasmopara viticolainfection risk management in north-west Spain

Abstract: The climate of north-western Spain, with high temperatures and relative humidity during the grapevine vegetative cycle, can especially favour the development of fungal diseases in vineyards. One of the most important diseases is downy mildew, caused by the fungus Plasmopara viticola. The aim of the current study is to propose a system containing phenological data, biological sensors of pathogen indicator and the agrometeorological Goidanich Index in order to optimize the application of downy mildew fungicide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…In our study area, the Erysiphe and Plasmopara infections were later than the Botrytis, between the end of flowering (S-6) and development of fruits (S-7). These results agree with findings by other authors [57][58][59]. Generally, powdery mildew requires relatively dry conditions and moderate temperatures, while downy mildew is greatly affected by wet conditions, either the presence of dew or rainfall [60].…”
Section: Relationship With Phenological Stage and Meteorological Inflsupporting
confidence: 92%
“…In our study area, the Erysiphe and Plasmopara infections were later than the Botrytis, between the end of flowering (S-6) and development of fruits (S-7). These results agree with findings by other authors [57][58][59]. Generally, powdery mildew requires relatively dry conditions and moderate temperatures, while downy mildew is greatly affected by wet conditions, either the presence of dew or rainfall [60].…”
Section: Relationship With Phenological Stage and Meteorological Inflsupporting
confidence: 92%
“…Concerning airborne P. viticola sporangia, the current study confirmed other reports that P. viticola sporangia are a common component of the airborne microflora of vineyards ( Diaz et al, 1998 ; Albelda et al, 2005 ; Fernandez-Gonzalez et al, 2009 ; Magyar et al, 2009 ; Fernández-González et al, 2011 , 2019 ; Martínez-Bracero et al, 2019 ; Rodríguez et al, 2020 ). This is highly relevant to DM management: while the inoculum for primary infection is available only following a rain, the secondary inoculum is always present when P. viticola is established in the vineyard.…”
Section: Discussionsupporting
confidence: 90%
“…The next model step consists of DM-free sites on which the sporangia deposit after being detached from sporangiophores on sporulating DM lesions and dispersed into the air ( Figure 1 ). Because P. viticola sporangia become airborne under a wide range of environmental conditions ( Caffi et al, 2013a ) and because they are normally present in the air of DM-affected vineyards ( Diaz et al, 1997 , 1998 ; Albelda et al, 2005 ; Fernandez-Gonzalez et al, 2009 ; Magyar et al, 2009 ; Fernández-González et al, 2011 , 2019 ; Martínez-Bracero et al, 2019 ; Rodríguez et al, 2020 ), the model assumes that whenever there are sporangia on DM lesions, sporangia may detach, disperse, and be deposited on the host surface, i.e., when D’ > 0; if D’ = 0, there are no viable sporangia, and the model run ends.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the identification and quantification of the spore load in the atmosphere as bioindicators of pathogen presence, and their relationship with the meteorological and geographical data allows us to prevent the frequency and severity of diseases early [58]. Several studies detected a high degree of association between the aerial conidia concentration and the lesion density of the plants one week later, which shows the relation of disease development with spore concentrations in the atmosphere of the crop during previous periods [59][60][61]. The learning of the different ecological processes behavior of phytopathogenic fungus in the atmosphere of the crop is very important in regions where the cultivated area tend to the increase before the pressure of disease could be high.…”
Section: Discussionmentioning
confidence: 99%